Modeling of PD Behavior - Norasage Pattanadech; Rainer Haller; Stefan Kornhuber; Michael Muhr (My University, 2023)
For deeper understanding and interpretation of partial discharge (PD) measurement results as well as verification of recognized PD phenomena, various models of PD behavior mostly based on equivalent circuits have been developed. This chapter describes PD models for internal discharges as well as gliding and external discharges. The current applied models can be mainly classified into two groups – the modeling based on equivalent circuit, or so-called network-based model, and the modeling based on physical relations of electric field within the insulation, or so-called field-based model. The traditional network-based PD model describes the measurable PD transients on the electrodes of the insulation system with a discharge of an internal virtual capacity representing the defect. The field-based PD model explains the discharge phenomena based on physics of gas discharge and enables an analytical treatment of the PD transients.
Keywords: High voltage insulation and dielectric phenomena; Electrostatic Discharge in Electronics; Plasma Diagnostics and Applications